2019
DOI: 10.1037/men0000177
|View full text |Cite
|
Sign up to set email alerts
|

Threatened-masculinity shame-related responses among straight men: Measurement and relationship to aggression.

Abstract: The significant sex-based discrepancy in violent crime suggests that something about maleness or masculinity contributes to this pattern. Research on masculinities clearly indicates that if men struggle to meet masculine gender role expectations, they are likely to report distress (Eisler & Skidmore, 1987; O’Neil, 2008). Empirical work demonstrates that failing to meet these expectations causes some men to become aggressive (Vandello & Bosson, 2013), but literature has not fully elucidated the psychological ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 77 publications
(99 reference statements)
2
13
1
Order By: Relevance
“…This study depicted a man failing to uphold prescriptive ideals around male aggression and dominance, as the victim submitted to a verbal directive without physically resisting or escaping. As a result, this study was inconsistent with Gebhard et al (2018) who found that externalization of blame mediated the relationship between shame-proneness and threatened-masculinity. Our findings suggest that shame proneness is associated with a reduction in blame attributions among men and, consequently, that shame may foster sympathy toward other men.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This study depicted a man failing to uphold prescriptive ideals around male aggression and dominance, as the victim submitted to a verbal directive without physically resisting or escaping. As a result, this study was inconsistent with Gebhard et al (2018) who found that externalization of blame mediated the relationship between shame-proneness and threatened-masculinity. Our findings suggest that shame proneness is associated with a reduction in blame attributions among men and, consequently, that shame may foster sympathy toward other men.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, externalization of blame has been shown to mediate the relationship between shame proneness and aggression (Stuewig et al, 2010). For men specifically, this relationship has been found in connection to feelings of threatened masculinity among heterosexual men (Gebhard et al, 2018). Given these findings, it is plausible that shame-prone men attribute more blame to male victims given that the act of disclosure violates norms of masculinity.…”
mentioning
confidence: 98%
“…In a recent advance, Gebhard et al (2019) addressed the individual difference question by developing a measure of threatened-masculinity shame-related responses, the Masculinity and Shame Questionnaire (MASQ). The MASQ is a scenario-based measure of shame-related responses to threatened masculinity.…”
Section: An Extension Of the Grsp To Account For Gun Violencementioning
confidence: 99%
“…The MASQ is a scenario-based measure of shame-related responses to threatened masculinity. It presents hypothetical threatened masculinity scenarios (e.g., “You take a highly regarded personality test and the results indicate that your personality is more feminine than masculine,” Gebhard et al, 2019, p. 442) and asks respondents to rate how likely they would be to respond in one of four ways: feel shame, escape, prevent exposure, and externalize blame. The investigators found a linkage between threatened-masculinity feel-shame responses and self-reports of a tendency to be physically aggressive.…”
Section: An Extension Of the Grsp To Account For Gun Violencementioning
confidence: 99%
“…The reason for this result is unclear, as threat demonstrates a stronger negative relationship with positive constructs (e.g., self-esteem; Burkley et al, 2016). Perhaps threat is more relevant to constructs that involve social comparison (e.g., shame; Gebhard et al, 2019), whereas boost is more related to internal perceptions of mental health. Nevertheless, more research should explore the relationships between contingency subscales and positive constructs to better understand these relationships.…”
Section: Discussionmentioning
confidence: 99%